Are Longer and Heavier Vehicles (LHVs) Beneficial for Society? A Cost Benefit Analysis to Evaluate their Potential Implementation in Spain (2014)
In this paper we carry out a thorough review of the current research related to the benefits and costs arising from the implementation of longer and heavier vehicles (LHVs). From this review we concluded that despite the many studies available, little has been said about the sensitivity of the benefits and costs to the ultimate performance of the key variables related to the evolution of the economy, road transport performance, safety, and so on. In order to fill this gap, we have designed a sensitivity approach based on a cost benefit analysis tool to determine which variables demonstrate the greatest influence on the benefits and costs stemming from the implementation of LHVs. In order to test the methodology, we have used it in an analysis of the Spanish trunk network. The results show that the benefits of LHVs for society are significant. Even in the least favorable scenario, the economic benefits are greater than €3500 million over 15 years, and the environment enhanced as well, for CO2 emissions are reduced by 2 Million tonnes. Overall we noted how the results are not very sensitive to the evolution of key variables in determining the final outcome. However, we found that the variables that have the greatest affect on the final benefit, such as traffic growth and social discount rate, depend basically on the performance of the overall economy. Moreover, the private cost for haulers seems to be more important in determining the final benefit than externality costs.